USING PODCASTS TO IMPROVE LISTENING AND SPEAKING SKILLS IN EFL CLASSES - Sayyora Ilxomiddin Qizi Bozorova; Maftuna Raxmonovna Boboyorova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Listening and Speaking skills have been becoming dominant in terms of necessity among other skills while learning and teaching English as a foreign language. In order to communicate properly every single language learner who is learning a foreign language have to develop these skills. However, while learning and teaching those skills they have been having difficulties. Definitely, podcasts have enough benefits for students to learn a foreign language , but they need to use them with proper methods. This article explained how podcasts can be helpful for students to boost listening and speaking skills. Also, it has recommended to improve listening and speaking skills by the help of podcasts and has shown ways how to use them while learning and teaching a foreign language.